2021
DOI: 10.3390/ijerph18073407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Performance in a Maximum Effort Test for Lifeguards and the Time Spent in a Water Rescue

Abstract: The main objective of this study was to analyse the relationship between the performance in a maximum incremental test for lifeguards, the IPTL, and the effectiveness of a 200 m water rescue on the beach. Initially, 20 professional lifeguards carried out the IPTL in the pool and then they performed a 200 m water rescue on the beach. The maximum oxygen uptake (VO2max) in the IPTL was estimated. In both tests, heart rate (HR), blood lactate (La) and time achieved were measured. The VO2max estimated in the IPTL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…While lactate results do not show significant differences, it is interesting to note that efforts are above the considered anaerobic threshold, indicating a type of lactate anaerobic effort [ 29 , 30 ]. In this study, the mean lactate values reached were close to or lower than those obtained in other studies with lifeguards that conducted various trials comparing materials or rescue conditions [ 7 , 8 , 31 , 32 ]. The differences may be due to the fact that in the present study, all the rescuers used wetsuits, which helped them to reduce resistance to advance and achieve a lower lactate accumulation [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…While lactate results do not show significant differences, it is interesting to note that efforts are above the considered anaerobic threshold, indicating a type of lactate anaerobic effort [ 29 , 30 ]. In this study, the mean lactate values reached were close to or lower than those obtained in other studies with lifeguards that conducted various trials comparing materials or rescue conditions [ 7 , 8 , 31 , 32 ]. The differences may be due to the fact that in the present study, all the rescuers used wetsuits, which helped them to reduce resistance to advance and achieve a lower lactate accumulation [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…The quantification of good CPR in a simulation with manikins has been arbitrarily assumed to be equal to or higher than a value of 70% [ 34 ]. One possible explanation is that rescuers have comprehensive training which includes endurance and strength capabilities [ 35 ], and their work also specifically requires training in both the lower and upper limbs (including hand muscles), in addition to good physical health to allow CPR to be performed [ 36 ] even to allow CPR to be performed under conditions of previous fatigue [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that endurance exercise training enhances rescuers' resistance to fatigue, but a rescuer towing a diver may need to exercise at a higher intensity to increase the exercise tolerance [3,9,10]. Maximal oxygen uptake (V@ O2max,) and the lactate concentration (LA) during exercise are important indicators of lifeguards endurance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the technical and physical skills of lifeguards have been extensively studied in previous research data, there are few studies identifying physiological factors associated with improving the lifeguard cardiopulmonary performance [2,8,9]. From a physiological point of view, exercise training has the potential to strengthen muscle contraction, improve oxygen capacity, and therefore, the effectiveness of cardiopulmonary resuscitation intervention [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation